Development of a power evaluation system for combat sports, based on load cell and elastic band - Vieira Sarmet Moreira, P.; Luporini Menegaldo, L. (XXVI Brazilian Congress on Biomedical Engineering, 2019)
The training with elastic bands are very used for training muscle power, however, usually the values of power output are not quantified. This turns totally subjective the process of choice for the rigidity, diameter, length and number of elastics to be used by each athlete. The aim of the present study was to develop a power evaluation system for performance measurements of martial techniques. For this purpose, elastic bands were connected to a load cell, where the elastic constants were properly calibrated through a 2nd order exponential equation with R2 Adjusted = 1.00 and p < 0.001. Following the system was used to evaluate the optimal load for specific power development during taekwondo kicks. As a result this system presented very satisfactory results, since for the valid kicks, the information about the initial strain level of the elastics in which the highest power and force was obtained was quite easy to obtain. In addition, the system demonstrated in this study presents very useful, easy-to-use and fast processing solutions to monitor the performance of athletes at different stages of sports training periodization.